Atividades práticas em sequências didáticas de ciências: oficina de formação de professores dos anos iniciais do ensino fundamental - Ribeiro, Andréia Viana (2025)
This paper discusses the importance of using practical activities as more contextualised methods, using a variety of resources, to engage students in the Early Years of Primary School in the subject of Science. The proposal consisted of drawing up a didactic sequence, applying practical activities, sharing materials and methodologies used for teachers to work with in the classroom or to use as a model for other scientific content. That said, the general aim of this work was to analyse the possibilities and limits of a workshop on practical science activities for the training of primary school teachers. To this end, a bibliographical survey was carried out on practical activities and their importance in science teaching, as well as on didactic sequences. A workshop was then developed and carried out with teachers from a municipal public school in Fortaleza, covering practical activities and didactic sequences for the Early Years of Primary School. The workshop was aimed at contextualisation, the use of didactic strategies and language closer to the reality and age group of the students, valuing the context of the school and classroom activities, as well as exploring different methodologies, resources and examples of practical activities applied in a didactic sequence. Analysing the data collected during the workshop (by means of questionnaires and a logbook with observations on the participation and preparation of a didactic sequence by the participating teachers) made it possible to identify: the teachers' conceptions of the use of different methodologies and activities that make students the protagonists in science teaching; the difficulties encountered in implementing practical activities due to the lack of research material; and the potential of this approach for student learning. As a result, an educational resource was produced, a practical guide for a teacher training workshop, which contains suggestions for activities and resources to help them develop their own teaching sequences. The research revealed that the training workshop is an important space for reflection on teaching practice and for building knowledge about science teaching through practical activities. Limitations include the difficulty teachers have in accessing up-todate scientific knowledge and the lack of appropriate pedagogical training to deal with this content.